EVALUASI PELAKSANAAN PEMBELAJARAN DARING OLEH GURU AKUNTANSI KELAS X SMK PANCA BHAKTI SUNGAI RAYA - YULIANI, RANI; Asriati, Nuraini; Genjik, Bambang (Universitas Tanjungpura, 2023)
This study aims to determine the suitability of the learning implementation plan with the implementation of learning as well as the suitability of planning and implementation with applicable online learning implementation standards. This research was conducted at SMK Panca Bhakti Sungai Raya Kab. Royal stronghold. The method used in this study is a descriptive method with a qualitative research form The data studied in this study were sourced from the class X Accounting teacher at SMK Panca Bhakti Sungai Raya. Data collection techniques used are observation, interviews and documentary studies. The criteria in this study refer to the standard process of implementing online learning. The results showed that 1) From the aspect of planning (antecendents), an online learning implementation plan (RPP) had been prepared by an Accounting teacher for class X SMK Panca Bhakti Sungai Raya in accordance with the Circular Letter of the Minister of Education and Culture Number 14 of 2019 concerning Simplification of Learning Implementation Plans (RPP). 2) In the process aspect (transaction), the implementation of online learning by the class X Accounting teacher at SMK Panca Bhakti Sungai Raya has been carried out by the teacher by referring to SE Number 15 of 2020 concerning Guidelines for Organizing Learning From Home. However, the teacher has not been fully able to carry out learning in accordance with the guidelines. 3) Aspects of outcomes (outcomes), the teacher plans learning in accordance with the standard process, but in reality there is still a learning implementation that is not in accordance with the Learning Implementation Plan that has been prepared.